2017
DOI: 10.1021/acsomega.7b01219
|View full text |Cite
|
Sign up to set email alerts
|

Dual Probe Sensors Using Atomically Precise Noble Metal Clusters

Abstract: This article adds a new direction to the functional capability of protein-protected atomically precise gold clusters as sensors. Counting on the extensively researched intense luminescence of these clusters and considering the electron donating nature of select amino acids, we introduce a dual probe sensor capable of sensing changes in luminescence and conductivity, utilizing bovine serum albumin-protected atomically precise gold clusters hosted on nanofibers. To this end, we have also developed a hybrid nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…[1][2][3][4][5] Such exquisite control endows nanomaterials many new properties for applications in optics, catalysis, sensing, biology, and biomedicine. [6][7][8][9][10][11] Programmable nanomaterials were first achieved in controlling the assembly of NP building blocks. [12][13][14][15] The nature of DNA base pairing and programmability allowed the creation of programmable nanomaterials, [16][17][18][19] which was achieved when applying DNA oligonucleotides to colloidal Au.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Such exquisite control endows nanomaterials many new properties for applications in optics, catalysis, sensing, biology, and biomedicine. [6][7][8][9][10][11] Programmable nanomaterials were first achieved in controlling the assembly of NP building blocks. [12][13][14][15] The nature of DNA base pairing and programmability allowed the creation of programmable nanomaterials, [16][17][18][19] which was achieved when applying DNA oligonucleotides to colloidal Au.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of interest to explore a family of stable silver NCs with tunable properties. Various physicochemical properties such as narrow energy gap and associated multiple electronic transitions, luminescence, chirality, etc., have been used in numerous fields, including optoelectronics, nanosensors, nonlinear optics, circularly polarized luminescence, and nanocluster sensitized solar cells, etc. Different silver NCs have been characterized through mass spectrometric studies. However, some of them, such as Ag 6 , Ag 9 , Ag 25 , Ag 29 , Ag 44 , Ag 56 , Ag 67 , and Ag 141 , etc., with specific ligand structure and overall charge, have also been characterized structurally using single crystal X-ray diffraction. Some recent studies have also reported synthesis and structural characterization of bimetallic and polymetallic NCs following coreduction of mixed metal precursors and intercluster reactions. Different transition metal-doped silver NCs, especially Ti and Cd, with varying numbers of dopant atoms showed different electronic features in comparison to the undoped ones. , During crystallization of nanoclusters, more than one silver NC was crystallized within the same unit, forming cocrystals, such as Ag 16 –Ag 17 , Ag 40 –Ag 46 , Ag 210 –Ag 211 , etc. A detailed understanding of their synthesis, and associated structures, and properties has become an important research direction.…”
Section: Introductionmentioning
confidence: 99%
“…This favors the formation of a Au 30 core inside a BSA molecule. This cluster was previously reported and studied with different techniques. ,, We followed the same ratio of metal ion/protein concentration during electrospray synthesis. As a result, the Au 30 core was formed.…”
Section: Resultsmentioning
confidence: 99%